Why is corruption so widespread in the character and conduct of so many Peruvians? - Perales, Alberto (2018)
When in the 80s and 90s, I published several articles that identified the three main mental health problems in Peru: 1) poverty and underdevelopment, 2) widespread corruption and 3) violence1,2,3 I did not imagine the depth with which the second of them, corruption, eroded the institutional structure of the State, the democratic system and the social fabric of our country. In this regard, I do not need to provide evidence because they flow unchecked by all the observable levels of our society, from the highest to the most humble, as if the Peruvians, for the first time, had managed to agree on something, to tell Manuel Gonzales Prada who was right: "In Peru, where you put your finger jumps the pus."